Detection and Characterization of Catechol Quinone-Derived Protein Adducts Using Biomolecular Mass Spectrometry - Chen, Shu-Hui; Li, Chun-Wei (Frontiers in Chemistry, 2019)
Catechol quinone (CQ) motif is found in many biologically relevant molecules throughout endogenous metabolic products, foods, drugs, and environmental pollutants. CQ derivatives may undergo Michael addition yielding covalent bonds with nucleophilic sites of biomolecules such as cysteine, lysine, or histidine residue of proteins. The CQ-adducted proteins may exhibit cytotoxic actions or biological functions different from their un-adducted form. Identification, characterization, and quantification of relevant protein targets are essential but challenging goals. Mass spectrometry (MS) is well suited for the analysis of protein and protein modifications. Bottom-up proteomics as a key driver for technological development has benefitted the field of biomolecular MS including protein adductomics. This mini-review will focus on the use of biomolecular MS in 1. structural and functional characterization of CQ adduction of protein standards; 2. identification of adduction targets or adduction-induced changes; 3. quantification of adducted proteins as exposure index. Technical advances in sample preparation, MS instrumentation, and software to facilitate protein adductomics will be discussed. Various CQs derivatives including endogenous dopamine and catechol estrogens as well as food/drug-derived polyphenols which form covalent protein adducts are included.